Positive or Preventive? Reproduction in Taiwan and the Netherlands, 1850-1940 - Ying-chang, Chuang (Life at the Extremes: The Demography of Europe and China, 2006)
This book adresses an important issue in historical demography - the differences between reproduction in low pressure and high pressure demographic regimes. The existence of such differences was first noted in 1789 by Thomas Malthus when he contrasted the low pressure European regimes with the high pressure regimes found in the less civilized parts of the world, most notably China and Japan. This contrast, long taken as fundamental by historical demographers, has recently been challenged by authors who argue that it should be discarded as Malthusian mythology. The papers included here evaluate the received and revisionist views by comparing reproduction in a high pressure regime - Taiwan during the Japanese occupation - and a low pressure regime - the Netherlands in the years 1830-1920. The papers examine the impact of infant mortality, social class, ethnic identity, illegitimacy, form of marriage, and rural vs. urban settings. Reality or mythology?, that is the question.